2021
DOI: 10.3390/met11071080
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Understanding of the Environmental Effect on B10 Copper Alloy Corrosion in Seawater

Abstract: Corrosion in natural seawater is difficult to simulate in a laboratory due to the slow rate and complexity of the corrosion process which involves multiple influential factors. This paper aims to explore the quantitative effect of environmental factors on corrosion process and find the best experimental conditions which represent the actual environment and have the best acceleration effect. A new framework is followed in this paper which consists of three parts: design of experiments, outdoor and laboratory co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Specimens can be immersed in actual seawater from a coastal area to simulate natural conditions [73]. Alternatively, synthetic seawater solutions can be prepared to mimic the composition of natural seawater.…”
Section: Corrosion Simulationmentioning
confidence: 99%
“…Specimens can be immersed in actual seawater from a coastal area to simulate natural conditions [73]. Alternatively, synthetic seawater solutions can be prepared to mimic the composition of natural seawater.…”
Section: Corrosion Simulationmentioning
confidence: 99%
“…Copper heat exchangers usually operate at room temperature to about 80 • C. Water temperature is an important factor for the corrosion resistance of copper pipes. There are many reports about the influence of temperature on the corrosion behavior of copper [6][7][8][9]. Rahman et al [7] studied the corrosion of copper heat exchangers in river water and seawater at different temperatures for 30 d. They found that the corrosion rate and ion conductivity increase with the solution temperature from 20 to 80 • C. Ren et al [8] studied the effect of dissolved oxygen in tap water on copper corrosion under temperatures of 30 to 50 • C. The increase in temperature results in a lower oxygen solubility and a larger oxygen diffusion coefficient, which produces the highest corrosion rate at about 40 • C for copper.…”
Section: Introductionmentioning
confidence: 99%
“…Rahman et al [7] studied the corrosion of copper heat exchangers in river water and seawater at different temperatures for 30 d. They found that the corrosion rate and ion conductivity increase with the solution temperature from 20 to 80 • C. Ren et al [8] studied the effect of dissolved oxygen in tap water on copper corrosion under temperatures of 30 to 50 • C. The increase in temperature results in a lower oxygen solubility and a larger oxygen diffusion coefficient, which produces the highest corrosion rate at about 40 • C for copper. Cai et al [9] reported that the corrosion rate of the copper alloy B10 in seawater noticeably decreases with the change in temperature from 25 to 60 • C due to the reduction in dissolved oxygen by about 39%. Lytle et al [6] found that the copper pipelines of their testing community showed pitting leakage in cold water, but almost no leakage in hot water.…”
Section: Introductionmentioning
confidence: 99%
“…The exploitation of marine resources is inseparable from marine equipment, meaning that a large number of metal materials need to serve in the marine environment [1][2][3]. As we all know, there are many kinds of inorganic salts in seawater with an average salinity of 35, which makes seawater a natural strong electrolyte [4][5][6][7]. Therefore, metal materials often suffer serious corrosion in the marine environment.…”
Section: Introductionmentioning
confidence: 99%